PERANCANGAN KOMPOR LISTRIK BERBASIS PANEL SURYA TERHADAP PENGARUH PANJANG COIL - Moh. Wahyu Aminullah; Haryadi Haryadi; Dina Fitria (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2022)
Solar energy can be obtained easily and free of charge, but the conversion results are not entirely easy and free. In this study we tried to develop alternative energy from sunlight or solar panels as an energy source that can produce electrical energy (DC) as an energy source for electric stoves. The induction electric stove was self-assembled in this study with a cross-sectional area of ​​10 cm2. In testing the induction electric stove was used to heat water for 15 minutes. The test was carried out from 09:00 – 15:00 for 3 days using a coil with various coil lengths (1m, 2m, and 3m). The results showed that the coil length of 1 m resulted in the lowest inductance value of 125.6 x 10-9 H, and the lowest power of 119,025 Wh. While the coil with a length of 3 m produces the best inductance value of 376.8 x 10-9 H, and the best power of 125.235 Wh. The results showed that the greater the coil length value, the greater the inductance and power generated.